3D human heart modeling (self-organizing Map Neural Network) / Mohd. Tharmezy Md. Tajuddin - Mohd. Tharmez, Md. Tajuddin (2003)
Kohonen has developed an algorithm with self-organizing properties for a network of adaptive elements. These elements receives signal from an event space and the signal representations are automatically mapped onto a set of output responses in such way that these responses acquire the same topological order as that of the primary events. In human heart modeling process, segmentations is the most important thing before create the 3 dimensional modeling of human heart. Heart images from the source can be processed t become the signal for the Self-Organizing Maps (SOM) network and the output neuron that have adapted to the images, present interesting features such as contour-extractions and edge detections. In this work the Neural Network applications specific to the Self-Organizin network used to segmenting the human heart images to produced the 3 dimensional modeling of human heart.